in 40 minutes it will be 12:10
Solve for e
7(2e-1)-11=6+6e
7×2=14e
7×1=7
14e-7-11=6+6e
-6e -6e
8e-7-11=6
+7 +7
8e-11=13
+11 +11
8e=24
8e÷8=e
24÷8=3
e=3
To solve the equation 7(2e-1)-11=6+6e for e, distribute, combine like terms, subtract, add, and divide until you have isolated e. The solution is e=3.
Explanation:To solve for e in the equation 7(2e-1)-11=6+6e, first distribute the 7 on the left side of the equation:
14e - 7 - 11 = 6 + 6e
Now, combine like terms on both sides:
14e - 18 = 6 + 6e
Next, subtract 6e from both sides:
8e - 18 = 6
Add 18 to both sides:
8e = 24
Finally, divide by 8:
e = 3.
Learn more about Equation Solving here:https://brainly.com/question/18262581
#SPJ2
step by step explanation please :-D
Solve the equation. Check for extraneous solutions.
9|9 – 8x| = 2x + 3
To solve an absolute value equation of the form |X| = k, where X is an expression with a variable and k is a non-negative number or an expression, you must solve the compound equation X = k or X = -k.
The first step is to divide both sides by 9 to get the absolute value of an expression equal to a non-negative number.
9|9 – 8x| = 2x + 3
Divide both sides by 9.
[tex] |9 - 8x| = \dfrac{2x + 3}{9} [/tex]
Now we eliminate the absolute value by rewriting this as a compound equation.
[tex] 9 - 8x = \dfrac{2x + 3}{9} ~~~or~~~ 9 - 8x = -\dfrac{2x + 3}{9} [/tex]
We must solve both equations.
Multiply both sides by 9.
[tex] 9(9 - 8x) = 2x + 3 ~~~or~~~ 9(9 - 8x) = -(2x + 3) [/tex]
[tex] 81 - 72x = 2x + 3 ~~~or~~~ 81 - 72x = -2x - 3 [/tex]
[tex] -74x = -78 ~~~or~~~ -70x = -84 [/tex]
[tex] x = \dfrac{-78}{-74} ~~~or~~~ x = \dfrac{-84}{-70} [/tex]
[tex] x = \dfrac{39}{37} ~~~or~~~ x = \dfrac{6}{5} [/tex]
Answer: x = 39/37 or x = 6/5
To check for extraneous solutions, we plug in each solution into the original equation and check if it works.
Check 39/37:
9|9 – 8(39/37)| = 2(39/37) + 3
|81 - 72(39/37)| = 78/37 + 3
|2997/37 - 2808/37| = 78/37 + 111/37
|189/37| = 189/37
189/37 = 189/37
The solution 39/37 is valid.
Check x = 6/5.
9|9 – 8x| = 2x + 3
9|9 – 8(6/5)| = 2(6/5) + 3
|81 - 72(6/5)| = 12/5 + 15/5
|405/5 - 432/5| = 27/5
|-27/5| = 27/5
27/5 = 27/5
The solution x = 6/5 is also valid.
There are no extraneous solutions.
How do you get x with steps?
Lara made some chocolate tarts. For every 5 cups of chocolate chips, she added 3 cups of sugar. The ratio of chocolate chips to sugar in Lara’s chocolate tarts is ____.
5 over 3
3 over 5
3
5
use the amount for each quantity to obtain theratio
choc chips : sugar = 5 : 3 = [tex]\frac{5}{3}[/tex]
Answer:
[tex]\frac{5}{3}[/tex]
Step-by-step explanation:
Please help me solve this, and show your work
6r + 5 = 11r
&
2x-4
---------- = 6x+3
2
[tex]6r+5=11r\ \ \ \ |\text{subtract 6r from both sides}\\\\5=5r\ \ \ \ |\text{divide both sides by 5}\\\\\boxed{r=1}\\-------------------------\\\dfrac{2x-4}{2}=6x+3\\\\\dfrac{2x}{2}-\dfrac{4}{2}=6x+3\\\\x-2=6x+3\ \ \ \ \ |\text{add 2 to both sides}\\\\x=6x+5\ \ \ \ |\text{subtract 6x from both sides}\\\\-5x=5\ \ \ \ \ |\text{divide both sides by -5}\\\\\boxed{x=-1}[/tex]
differentiate f(x)=x^2sin(x)
Answer:
[tex]\displaystyle \large{f\prime(x) = 2x \sin (x) + x^2 \cos (x)}[/tex]
Step-by-step explanation:
We are given a function:
[tex]\displaystyle \large{f(x) = x^2 \sin (x)}[/tex]
Notice that there are two functions multiplying each other. Recall the product rules.
[tex]\displaystyle \large{y=h(x)g(x) \to y\prime = h\prime (x) g(x) + h(x)g\prime (x)}[/tex]
You can let x^2 = h(x), sin(x) = g(x) or sin(x) = h(x), x^2 = g(x) as your desire but I’ll let h(x) = x^2 and g(x) = sin(x).
Therefore, from a function:
[tex]\displaystyle \large{f(x) = x^2 \sin (x) \to f\prime (x) = (x^2)\prime \sin(x) + x^2 (\sin (x))\prime}[/tex]
Recall the power rules and differentiation of sine.
[tex]\displaystyle \large{y = ax^n \to y\prime = nax^{n-1} \ \ \ \tt{for \ \ polynomial \ \ function}}\\ \displaystyle \large{y = \sin (x) \to y\prime = \cos (x) }[/tex]
Therefore, from differentiating function,
[tex]\displaystyle \large{f\prime(x) = 2x \sin (x) + x^2 \cos (x)}[/tex]
And we are done!
PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!
What is the factored form of the expression over the complex numbers?
121x^2 + 36y^2
Can i please get help with this question?
100 stickers are evenly divided between 16 children.How many stickers will each kid get
Add. 7/8+(−1/4) Enter your answer as a fraction, in simplified form, in the box.
you answer is 5/8 please mark as brainliest if you need more help with questions like this lemme know
Linley bought a set of 20 markets at the price of $6. What does 1 marker cost?
One marker would cost approx. $0.03
If E=[-1,0,1,2,3,4] and F=[3,4,5,6,7,8] what is E U F?
[tex]E=\{-1,\ 0,\ 1,\ 2,\ 3,\ 4\}\\\\F=\{3,\ 4,\ 5,\ 6,\ 7,\ 8\}\\\\E\ \cup\ F=\{-1,\ 0,\ 1,\ 2,\ 3,\ 4,\ 5,\ 6,\ 7,\ 8\}[/tex]
All elements from set E and from the set F. The same elements are only once.
To pay for sofa,maddie mad a payment of 64 dollers each month for one yar.How much did the sofa cost.
Explain why multiplying two irrational numbers could result in either an irrational number or a rational number.
Select the correct answer. The probability of event A is x, and the probability of event B is y. If the two events are independent, which of these conditions must be true? A. P(B|A) = y B. P(A|B) = y C. P(B|A) = x D. P(A and B) = x + y E. P(A and B) = x P(A) y
P(A) = probability of event A, P(B) = probability of event B
P(A) = x is given to us
P(B) = y is also given
--------------------------
If A and B are independent, then neither event affects the other. If we know A happens, then that doesn't change the probability of B happening (vice versa).
So that means P(A|B) = P(A) = x and P(B|A) = P(B) = y
This points to the answer being P(B|A) = y which is choice A or the first answer choice
note: P(A|B) is read as "probability of A given that B has happened". It is known as conditional probability. The symbol between the A and B is not the letter i or L, it is a vertical pipe symbol to separate the letters.
Probability of independent events will be P(A/B) = P(A) = x and P(B/A) = P(B).
What is probability?The probability of an event occurring is defined by probability.
Probability is also known as chance because, if you flip a coin, the likelihood that it will land on its head or tail is nothing more than the chance that either the head or the tail will occur.
In our daily time, there are several instances in the everyday world where we may need to draw conclusions about how everything will turn out.
The question is saying that event (A) and event (B) are independent it means
P(A/B) = P(A) is read by the probability of A after B events but for independent events, it doesn't matter.
P(B/A) = P(B) hence that will be the correct answer.
For more information about the probability
brainly.com/question/11234923
#SPJ2
Point p= -4 >>>> the distance between point q and point p is 6 1/2 units. Which number could represent point q
p = -4
q could be 6.5 units to the right ... or to the left ... of point p.
to the right: p + q ⇒ [tex]-4 + (6\frac{1}{2}) = 2\frac{1}{2}[/tex]
to the left: p - q ⇒ [tex]-4 - (6\frac{1}{2}) = -10\frac{1}{2}[/tex]
Answer: [tex]2\frac{1}{2}[/tex] or [tex]-10\frac{1}{2}[/tex]
Question : if 9999 = 4, 8888 = 8, 1816 = 6, 1212 = 0, then 1919 =?
The answer is:
1919=2
Step-by-step explanation:Let us assume the numbers as follows:
9=1
8=2
1=0
6=4
2=0
Hence, when we substitute the assumed values in each of the given numbers we obtain the result for each as follows:
1)
9999=1+1+1+1
9999=4
2)
8888=2+2+2+2
8888=8
3)
1816=0+2+0+4
1816=6
4)
1212=0+0+0+0
i.e.
1212=0
5)
1919=0+1+0+1
i.e.
1919=2
Answer
The value of 1919 is 2
Explanation:
Now find the value of 1919,
1 ⇒ 0
9 ⇒ 1
So, 1919 ⇔ 0101 ⇔ 0+1+0+1 = 2
Therefore, 1919 = 2
Further Explanation
Given, 9999= 4, 8888= 8, 8816= 6, 1212= 0,
If assume 9 as 1 for 9999 and add each 1 to get 4
So, 9999 ⇔ 1111 ⇔ 1+1+1+1 = 4
Therefore, 9 represents 1
If assume 8 as 2 for 8888 and add each 2 to get 8
So, 8888 ⇔ 2222 ⇔ 2+2+2+2 = 8
Therefore, 8 represents 2
If assume 1 as 0 and assume 6 as 2 for 8816 and add each digit to get 6
So, 8816 ⇔ 2202 ⇔ 2+2+0+2 = 6
Therefore, 1 represents 0 and 6 represents 2
If assume 2 as 0 for 1212 and add each digits to get 0
So, 1212 ⇔ 0000 ⇔ 0+0+0+0 = 0
Therefore, 2 represents 0
Learn More
Learn more about logical reasoning: https://brainly.com/question/8815372; Answered by: Empathictruro
Keywords
Logical reasoning, high school mathematics, numbers, mathematical sum
Fernando paid 2.80 for potatoes. Potatoes cost 25 cents per pound. How many pounds of potatoes dead fernando by?
Write as a decimal. Tell whether the decimal terminates of repeats. 1/6
Order the decimals 0.42, -1/2, 11/20, -0.51
least to greatest: -0.51, -1/2, 0.42, 11/20
greatest to least: 11/20, 0.42, -1/2, -0.51
Which are solutions to the equation x3 – 5x2 + 2x + 6 = 0? Round each solution to the nearest tenth. Check all that apply. X = –0.9 x = 0.8 x = 1.7 x = 4.2 x = 6.0
Given equation is [tex]x^3-5x^2+2x+6=0[/tex]
Usually we solve this type of problem by factoring but this equation is not factorable. If we solve by grouping then also we are not getting any common factor. So factoring method is not going to help. I this type of situation we may use graphing calculator. From graph we just need to pick those points where graph crosses the x-axis. Those values will be the final answer.
Using graphing calculator we see that there are three solutions at x=-0.856, x=1.678, x=4.177 which are approx x=-0.8, x=1.7 and x=4.2
Hence final answers are x=-0.8, x=1.7 and x=4.2.
Answer:
-0.9, 1.7, and 4.2
Step-by-step explanation:
Simplify fully. (refer to photo)
A.
B.
C.
D.
the answer to your question :[tex]4\sqrt{5}[/tex]
hope this helps! ❤ from peachimin
Exact Form:√5
Decimal Form:2.23606797…
what is the inverse of g(x)=(x-1)/4? is it g-1(x)=4x+1?
[tex]g(x)=\dfrac{x-1}{4}\to y=\dfrac{x-1}{4}\\\\\text{change x to y and y to x}\\\\x=\dfrac{y-1}{4}\ \ \ \ |\text{solve for y}\\\\\dfrac{y-1}{4}=x\ \ \ \ \ |\cdot4\\\\y-1=4x\ \ \ \ |+1\\\\y=4x+1\\\\\boxed{g^{-1}(x)=4x+1}[/tex]
If f(x)=2x-5 and g(x)=x^2-4x-8, find (f+g)(x).
[tex]f(x)=2x-5,\ g(x)=x^2-4x-8\\\\(f+g)(x)=f(x)+g(x)=(2x-5)+(x^2-4x-8)\\\\=2x-5+x^2-4x-8=x^2+(2x-4x)+(-5-8)=x^2-2x-13[/tex]
Answer:
[tex]\text{The value of (f+g)(x) is }x^2-2x-13[/tex]
Step-by-step explanation:
Given the two functions
[tex]f(x)=2x-5[/tex]
[tex]g(x)=x^2-4x-8[/tex]
we have to find the value of (f+g)(x)
As we know
[tex](f+g)(x)=f(x)+g(x)=(2x-5)+(x^2-4x-8)[/tex]
[tex]=2x-5+x^2-4x-8[/tex]
[tex]=x^2+2x-4x-5-8=x^2-2x-13[/tex]
[tex]\text{Hence, the value of (f+g)(x) is }x^2-2x-13[/tex]
which situation demonstrates the law of large numbers ?
a. if you roll a six-sides number cube 36 times, you will roll a 4 six times.
b. if 800 people are randomly surveyed about the TV shows they watch, about 400 of them will be women.
c. if you flip a coin 44 times, you will get heads about 22 times.
d.if it showed four days last month, it will snow four days this month.
The price of three t-shirt styles are $24, $30 and $36. The probability of choosing a $24 t-shirt is 1/6. The probability of choosing a $30 t-shirt is 1/2. The probability of choosing a $36 t-shirt is 1/3. What is the expected value of a t-shirt?
$29
$30
$31
$32
The law of large numbers in probability, is a theorem that describes the result of performing the same experiment a large number of times because the average of the results obtained from a large number of trials is close enough to the expected value.
So, according to this definition and the situation given , the correct answer is option B - if 800 people are randomly surveyed about the TV shows they watch, about 400 of them will be women; because there are larger number of experiment.
Part B:
To get the expected value of a t-shirt we will multiply each of the 3 prices by the associated probability, and then add up these three products-
[tex](24\times\frac{1}{6})+(30\times\frac{1}{2})+(36\times\frac{1}{3})[/tex]
=4 + 15 + 12 = $31
Hence, option C is correct.
Answer:
1. If 800 people are randomly surveyed about the TV shows they watch, about 400 of them will be women.
2. $31
Step-by-step explanation:
Got it right on the test.
Winning the jackpot in a particular lottery requires that you select the correct four numbers between 1 and 42 and, in a separate drawing, you must also select the correct single number between 1 and 30. Find the probability of winning the jackpot.
Answer:
[tex]\dfrac{1}{3,357,900}[/tex]
Step-by-step explanation:
There are
[tex]C^{42}_4=\dfrac{42!}{4!(42-4)!}=\dfrac{42!}{4!\cdot 38!}=\dfrac{38!\cdot 39\cdot 40\cdot 41\cdot 42}{2\cdot 3\cdot 4\cdot 38!}=39\cdot 10\cdot 41\cdot 7=111,930[/tex]
different ways to select the four numbers between 1 and 42. Only one of this ways is correct (successful to win).
There are 30 different ways select the single number between 1 and 30. Only one of them is correct.
The probability of winning the jackpot is
[tex]\dfrac{1}{111,930}\cdot \dfrac{1}{30}=\dfrac{1}{3,357,900}[/tex]
The probability of winning the jackpot in the particular lottery is 1 in 9,335,082,240.
Explanation:To find the probability of winning the jackpot, we need to calculate the probability of selecting the correct four numbers between 1 and 42 and the correct single number between 1 and 30.
For the four numbers, the probability of choosing each number correctly is 1/42 since there are 42 numbers to choose from and only one is correct. Since the selections are independent, we can multiply the probabilities together to get the overall probability of choosing all four numbers correctly: (1/42) * (1/42) * (1/42) * (1/42) = 1/311,169,408.
For the single number, the probability is 1/30 since there are 30 numbers to choose from and only one is correct.
To find the overall probability of winning the jackpot, we multiply the probabilities of selecting the four numbers correctly and the single number correctly: (1/311,169,408) * (1/30) = 1/9,335,082,240.
Learn more about Probability here:https://brainly.com/question/32117953
#SPJ3
Given 2x² = -8, x is .
Answer:
The values of x are : [tex]2i[/tex] and [tex]-2i[/tex]
Step-by-step explanation:
Given equation is: [tex]2x^2= -8[/tex]
First, we will divide both sides by 2 for getting rid of that 2 from the left side. So........
[tex]\frac{2x^2}{2}= \frac{-8}{2} \\ \\ x^2=-4[/tex]
Now, we need to take square root on both sides. So, we will get......
[tex]\sqrt{x^2}= \pm \sqrt{-4} \\ \\ x=\pm \sqrt{4(-1)} \\ \\ x=\pm 2\sqrt{-1}= \pm 2i[/tex]
(Replacing [tex]\sqrt{-1}[/tex] as [tex]i[/tex] )
So, the solutions are: [tex]x= 2i, -2i[/tex]
Answer:
2i or -2i
Step-by-step explanation:
There aré 23 students and a student admission ticket is 8$ how much will the student tickets cost
Tori bought a small container for paper clips in the shape of a right rectangular prism. The container had a height of 8 centimeters, a length of 4 centimeters, and a width of 3 centimeters. What volume can the container hold?
Today the ratio of elinor's age is 3:8 to his mother after 15 years ,the ratio will become 6:11. Find elinor's age today and find her mothers age after 15 years.
Given
ratio of elinor's age to his mother is 3 : 8
after 15 years
the ratio will become 6:11
Find out the elinor's age today and find her mothers age after 15 years.
To proof
As given in the question
ratio of elinor's age to his mother is 3 : 8
let x be the variable describe age.
let the elinor age = 3x
let the mother age = 8x
after 15 years
ratio will become 6:11
[tex]\frac{elinor\ age + 15 }{Mother\ age + 15 } = \frac{6}{11}[/tex]
As assume ealier elinor age be 3x and mother age be 8x
put this in the above equation
we get
[tex]\frac{3x + 15 }{8x + 15 } = \frac{6}{11}[/tex]
now sloving the above equation
we get
11 ( 3x + 15) = 6 ( 8x + 15 )
33x + 165 = 48x + 90
75 = 15x
[tex]x = \frac{75}{15}[/tex]
x = 5
Therefore
elinor's age today = 3x
= 3 × 5
= 15years
mothers age after 15 years = 8x + 15
= 8× 5 + 15
= 40 + 15
= 55years
Hence proved
The problem is about solving a system of equations established from the given ratios of Elinor's and her mother's ages. Substitution method is used to find their present ages, and to find mother's age after 15 years, we add 15 to her current age.
Explanation:This is a problem related to ratios and ages, which can be solved as an algebraic system of equations. Let's denote Elinor's present age as 'e' and her mother's age as 'm'. Then, from the problem we know that:
e/m = 3/8 (1), and
(e+15)/(m+15) = 6/11 (2).
From equation (1), we can express e as (3/8)m. We then substitute e in equation (2) to find the value of 'm'. Once we have 'm', we substitute its value in equation (1) to get 'e'. And to find her mother's age after 15 years, we add 15 to 'm'.
Learn more about Ratios and Ages here:https://brainly.com/question/29963980
#SPJ3